The types and prevalence of patholgies related to impacted mandibular third molars based on panoramic radiographs - Hari, Anisha Anil (University of the Witwatersrand, Johannesburg, 2024)
Introduction An impacted tooth may be defined as a pathological situation where the tooth is prevented from attaining a typical functional position. Impacted mandibular third molars are a frequent dental concern worldwide that may lead to a variety of other pathologies. This study aims to determine the prevalence and types of pathologies related to impacted mandibular third molars based on panoramic radiographs within a South African setting. Methods Panoramic radiographs were utilized to analyse pathologies related to impacted mandibular third molars through a cross sectional retrospective study. 600 radiographs were assessed. Patients of any age who were referred from the Maxillofacial and Oral Surgery department to the Radiology department for a panoramic radiograph relating to impacted mandibular third molars at Wits Oral Health Centre during a 5-year period from (2016 to 2020) were included in this study. Data was extracted by a single examiner to ensure diagnostic reproducibility. Results A total of 271 (45,0%) patients were female, and 329 (55,0%) patients were male. The patients' ages varied from 15 to 79 years old, with a mean age of 29,55 years. The age group between 20 and 29 years old (n = 288, 48,0%) had the highest frequency of pathology, followed by the 30-39-year-old age group (n = 219, 36,5%). Among all age groups, those over 50 represented the lowest percentage of pathology, with 8 individuals (1,3%). In terms of pathologies found, caries on the impacted third molar was the most prevalent (n=169, 28,1%) followed by caries on the adjacent second molar (n=136, 22,6%) while 72 patients presented with both caries on the impacted mandibular third molar as well as the adjacent second molar. 128 radiographs presented with peri-coronal radiolucent lesions. Periodontal bone loss accounted for 40 patients. Root resorption was the least prevalent pathology detected with a total of 4 patients. Conclusion The findings of this study along with parallels from the literature, indicates that caries is the most frequent pathology associated with impacted mandibular third molars. Caries may be seen on both the impacted third molar itself as well as the adjacent second molar and may be seen mostly between the ages of 30-49 years, with a higher predilection for males. Seeing that caries is so prevalent within the South African population, treatment or intervention of impacted mandibular third molars would be advisable.
A Research Report submitted in partial fulfillment of the requirements for the degree of Master of Science in Dentistry, in the Department of Maxillofacial and Oral Surgery.” School of Oral Health Sciences, University of Witwatersrand, Johannesburg 2024
Keywords: Pathologies; Third molars; Panoramic radiograph; UCTD; SDG-3: Good health and well-being